2013
DOI: 10.1177/0010414013488543
|View full text |Cite
|
Sign up to set email alerts
|

When the Stakes Are High

Abstract: The internet is changing the way Americans engage with information, whether they are choosing a president or making health care decisions. Two major drivers for this change are broadband adoption and personal motivation. First, an update: The Pew Internet Project estimates that between 75% and 80% of internet users have looked online for health information. We get slightly different results for the size of the e-patient population depending on our survey strategy, but these results are close enough to make us … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 54 publications
(77 reference statements)
0
20
0
Order By: Relevance
“…Assuming that political disagreements may lead to rhetorical attacks, we expect that the ideologically extreme are more negative in their campaigns than mainstream candidates. Results of previous studies do indeed suggest that parties far from the ideological centre are more inclined to go negative (Elmelund-Praestekaer, 2010;Walter et al, 2014). This logic leads to the following hypothesis: H3: Extreme candidates are more likely to use negativity than mainstream candidates.…”
Section: Why and Under Which Conditions Candidates Go Negativementioning
confidence: 81%
See 2 more Smart Citations
“…Assuming that political disagreements may lead to rhetorical attacks, we expect that the ideologically extreme are more negative in their campaigns than mainstream candidates. Results of previous studies do indeed suggest that parties far from the ideological centre are more inclined to go negative (Elmelund-Praestekaer, 2010;Walter et al, 2014). This logic leads to the following hypothesis: H3: Extreme candidates are more likely to use negativity than mainstream candidates.…”
Section: Why and Under Which Conditions Candidates Go Negativementioning
confidence: 81%
“…Outside this case, existing evidence is either on specific countries – such as Brazil ( da Silveira and de Mello, 2011 ) or Germany ( Maier and Jansen, 2015 ) – or, if comparative, often limited to only a handful of countries (e.g. Walter et al, 2014 ). A recent study ( Nai, 2018 ) compared the use of negative campaigning by candidates who competed in 35 national elections worldwide, but mostly focused on differences among the sponsors and the targets of the attacks, and only addressed the issue of cross-country comparison marginally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, studies showed that the relevance of negative campaigning varied with party characteristics. Especially opposition parties, parties that lose in the polls, parties with less coalition potential and those with less government experience are more likely to “go negative.” Conversely, negative campaigning is unusual for parties with governmental experience, with electoral fortune, and a positive coalition outlook, that is, established parties (Elmelund-Præstekær, 2010; Walter et al, 2014). Populist parties in particular seem to tend to engage in negative campaigning (Nai, 2018), although to a lesser degree when they see potential for future cooperation with certain mainstream parties or when they are in power (van Kessel and Castelein, 2016).…”
Section: Populist Party Support and The Impact Of External Efficacymentioning
confidence: 99%
“…Second, research in multiparty systems indicates that more ideologically extreme candidates attack more often than politically moderate actors (e.g., Elmelund-Præstekær 2010; Maier and Nai, 2021). The rational choice rationale is that extreme actors have a lower coalition potential, that is, are less likely to be considered for future coalition formation (Walter et al 2014). Therefore, they do not have to demonstrate that they are a congenial or compliant partner (Nai and Walter 2015) and thus are willing to take more risks.…”
Section: Theory and Hypothesesmentioning
confidence: 99%